Psychology of addiction - Boone, Delbert; Gary Whiteaker Corporation (Cahokia, IL : GWC, Inc., 1998)
(Producer) Addiction is an equal opportunity illness that can destroy its victims, understanding addiction is the key to recovery. Boone tells inmates at Albion Correctional Facility,'as you feed addiction it grows, as it grows, it dictates all terms of your life, and it never goes away.' he talks about the thousands of people who die from addiction each year, and how prisons are overflowing from drug related crimes. He tells them,'you are not in prison because you are bad people, you are here because you made bad choices while using alcohol and other drugs.'
Delbert Boone
Keywords: Substance-Related Disorders -- psychology; Alcoholism -- Psychology; Crime; Behavior, Addictive -- psychology